Detecting and Locating Signal Leakages from Cable TV Networks – A Case Study - Hussein Taha; Péter Vári (International Journal of Electronics and Telecommunications, 2023)
Since the digitalization of terrestrial television, many countries have discontinued television broadcasting in the UHF band. The freed-up frequencies are now available as digital dividends for mobile and fixed wireless access communication networks (MFCN), particularly for 4G/5G and public safety services in broadband called BBPPDR. Since cable TV still uses the UHF band, leakage from cable TV networks is the most common cause of interference in MFCN networks. Insufficient containment of the radio frequency signals transmitted through a cable system results in cable signal leakage. This article investigates the significance of controlling electromagnetic signal leaks from cable TV networks and how they impact authorized and standardized MFCN networks in the digital dividend bands. The periodic drivetest approach to detect and measure electromagnetic leakage from a cable TV system in the 700 MHz band at a site is detailed. The causes of the detected leaks and offered the appropriate procedure to repair them are also discussed. Additionally, the current measures taken in Hungary to address cable television signal leakage in the digital dividend bands are also discussed and alternative strategies for the adopted test drive approach are proposed.